Global Findex 2021رؤية تحليلية لفرص نفاذ الأفراد للخدمات المالية في الجزائر وبعض الدول العربية من خلال المؤشر العالمي - ورتي, شهرة; الحاج أحمد, فوزي (جامعة الوادي - University of Eloued, 2023)
الهدف من الدراسة هو ابراز وتحليل مدى نفاذ الافراد للخدمات المالية والمصرفية ومعرفة مستوى الشمول المالي في الجزائر وبعض الدول العربية وذلك من خلال دراسة وتقييم بعض المؤشرات المختارة وفقا للمؤشر العالمي للشمول المالي 2021. حيث توصلت الدراسة الى أنّ عدم تطور البنية التحتية وانخفاض معدل الانتشار المصرفي (الكثافة المصرفية) وضعف التثقيف المالي لدى الأفراد، عوامل انعكست على تدني مستويات الشمول المالي بالجزائر، وتوصي الدراسة باقتراحات لتوسيع قاعدة الاشتمال المالي وتعزيزها. The aim of the study is to highlight and analyze the extent of individuals for financial and banking services and to know the level of financial inclusion in Algeria and some Arab countries through the study and evaluation of some of the selected indicators in accordance with the global index of financial inclusion 2021. Where the study concluded that the lack of development of infrastructure, low rate of banking (banking density) and weak financial education in individuals, factors that reflected the low levels of financial inclusion in Algeria, and the study recommends suggestions to expand and enhance the base of financial inclusion.
An analytical Vision of individuals’ enforcement opportunities for financial Services in Algeria and some Arab countries through the international Index Global Findex 2021
مقال
Keywords: الشمول المالي ; الخدمات المالية ; Global Findex ; الدول العربية ; الجزائر; Financial inclusion: financial innovation،Global Findex؛ Arab Countries؛ Algeria